Pengaruh Pembiyaan Usaha Mikro Kecil Dan Menengah (Umkm) Dan Likuiditas Terhadap Resiko Pembiayaan Perbankan Syariah Di Indonesia Periode 2010-2014 - Wibisono, Achmadian Davin (AKRUAL: Jurnal Akuntansi, 2015)
Abstract The research study aims to analyze how the influence of Micro Small and Medium Enterprises (MSMEs) and Liquidity on the Financing Risk of shariah bank in Indonesia. This research using quantitative method with multiple linear regression analysis. The research result using data financial report and annual report by official website of shariah banks during period 2010-2014. These results indicate that Micro Small and Medium Enterprises (MSMEs) does not affect at the Financing Risk of shariah bank in Indonesia. Liquidity does not affect at the Financing Risk of shariah bank in Indonesia. Micro Small and Medium Enterprises (MSMEs) and Liquidity does not affect at the Financing Risk of shariah bank in Indonesia